Implementasi Penggunaan Alat Peraga Bola Kremes sebagai Alternatif Meningkatkan Hasil Belajar - Tri Palupi (LPPM IAINU Kebumen, 2020)
The problem of low learning outcomes for forward roll and back roll material skills is the basis for compiling research on best practice class VII E MTs Negeri 8 Semester, the learning of Physical Education Sports and Health (PJOK) in Kebumen implements the learning aids for learning ball crèmes as a PJOK learning strategy in an effort to improve the effectiveness and psychomotor learning outcomes or skills. The teaching and learning process can take place well if the teacher is able to manage the process in such a way as to produce quality learning. It is this principle of active and efficient learning that is expected to create an active, creative and fun PJOK learning atmosphere. One alternative that can be used is the application of the learning aids of the ball cremes in the learning process of forward roll and back roll floor gymnastics in PJOK subjects. The results of this best practice research show that students who have taken part in learning using the help of ball rolling learning aids have found it easier to master the forward roll and back roll movement because when students do the forward roll and back roll movement students always try to keep their head pressed against their neck to guard the ball. does not fall, so that it directly supports the movement of rolling forward and backward because the position of the head, body and legs remains round. The increase in psychomotor learning outcomes in the basic competence of floor gymnastics for Class VII E students was 40.63% from the initial test of 17 students to 30 students. So that the Implementation of the Use of the Kremes Ball Teaching Aid is proven to be able to improve Learning Outcomes of Material Skills For Forward Roll and Back Roll Floor Gymnastics for Grade VII E Students Even Semester 2019/2020 Academic Year. Key words: Kremes Ball Learning Aid, Kebumen 8th State Madrasah Tsanawiyah, Improving Learning Outcomes, PJOK Learning.